THE USE OF MIND MAPPING TECHNIQUE IN TEACHING VOCABULARY - Samhudi (Getsempena English Education Journal, 2015)
This research is aimed to describe the procedure of mind mapping technique on teaching vocabulary and to know the improvement of students’ vocabulary mastery after teaching learning vocabulary through mind mapping technique. In collecting the required data, the writer did test and questionnaire. The writer as teacher tried to apply mind mapping technique in teaching vocabulary mastery of students. The result of test show that mind mapping technique improved students’ vocabulary mastery. The result of the questionnaires show that most of the students agree that mind mapping is able to advance them, improve their vocabulary, expand their ideas, and increase their self confidence in learning.